2022
DOI: 10.3390/molecules27155016
|View full text |Cite
|
Sign up to set email alerts
|

A Review with Updated Perspectives on Nutritional and Therapeutic Benefits of Apricot and the Industrial Application of Its Underutilized Parts

Abstract: Fruits maintain the image as the richest sources of vitamins. Focusing on apricots, utilization of apricot species for many applications is possible due to its various benefits. Many research studies demonstrated different perspectives of apricot, especially in medical used as it can act as antioxidant, anti-inflammatory, and antimicrobial agents. Moreover, in the industrial sectors, apricots can be used in the production of biofuels and batteries. All components of the apricot fruit, including seeds and kerne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…The total sugar content ranged from 260.40 mg/g d.w in 'VM' to 744.59 mg/g d.w in 'SC', and the latter showed the highest TSS value (Table 2). In all accessions analyzed, the sugar content showed the following order: sucrose > glucose > fructose, confirming the order reported in previous works [26,[42][43][44]. Sucrose was the most concentrated sugar, ranging between 191.25 mg/g d.w in 'VM' and 553.26 mg/g d.w in 'SC', and the content of glucose ranged between 59.73 mg/g d.w in 'VM' and 243.04 mg/g d.w in 'PAN', while the fructose content ranged between 9.42 mg/g d.w in VM and 43.64 mg/g d.w in 'PAL'.…”
Section: Sugar and Acid Contentsupporting
confidence: 90%
See 1 more Smart Citation
“…The total sugar content ranged from 260.40 mg/g d.w in 'VM' to 744.59 mg/g d.w in 'SC', and the latter showed the highest TSS value (Table 2). In all accessions analyzed, the sugar content showed the following order: sucrose > glucose > fructose, confirming the order reported in previous works [26,[42][43][44]. Sucrose was the most concentrated sugar, ranging between 191.25 mg/g d.w in 'VM' and 553.26 mg/g d.w in 'SC', and the content of glucose ranged between 59.73 mg/g d.w in 'VM' and 243.04 mg/g d.w in 'PAN', while the fructose content ranged between 9.42 mg/g d.w in VM and 43.64 mg/g d.w in 'PAL'.…”
Section: Sugar and Acid Contentsupporting
confidence: 90%
“…Regarding the sourness of fruits, it depends largely on the relative amounts of sugars and organic acids present [47][48][49][50] and they are influenced by genotype, geographical location of cultivation, and fruit stage of maturity [27,44,46,51]. Table 5 shows the organic acid content in Vesuvian apricots analyzed.…”
Section: Sugar and Acid Contentmentioning
confidence: 99%
“…The apricots appear with holistic but also with targeted benefits upon the eye and stomach functions [44,45,[136][137][138]. The eye benefits are based on the large palette of carotenoids derivatives present in apricot fruits [139,140].…”
Section: Discussionmentioning
confidence: 99%
“…Studies regarding the antioxidant activity of the products from apricots indicated a high antioxidant potency [136][137][138]144,145]; the decrease in the reactive oxygen species scavenging efficacy after processing apricot fruits has also been established [146]. Concerning the antitumor activity, the highest interest of today is upon the extracts from the kernels of apricots since they contain a very active antitumor compound named amygdalin [44,45,147]. The fresh fruits, as well as the extracts from the apricots, both were proved to have antitumor potency [148]; an in vivo study [149] on rat groups exposed to radiotherapy and 7,12-dimethylbenz(a)anthracene/DMBA in order to induce tumors in liver showed that a daily supplementation of 20% apricot fruits counteracted the oxidative damage in treated rats; also, measurements showed a reduced level of alanine aminotransferase (ALT), aspartate aminotransferase (AST), 5 ′ -nucleotidase (5 ′ NT), malondialdehyde (MDA) and nitric oxide (NO), a reduced expression of B-cell lymphoma (Bcl-2) protein and of activator protein 1 (AP-1), of the cyclic AMP (cAMP) response element-binding protein (CREB) and of the cytokine nuclear factor kappa B (NF-κB) level in the treated rats; increases in the activity of the antitumor modulators Bax and caspase-3 appoptosis proteins and reduced glutathione (GSH) were also noticed, while the histopathological examinations of the liver samples revealed that mitosis, pericentral necrosis and pleomorphism caused by DMBA exposure in rats were mitigated after the apricot and/or radiotherapy administration [149].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that stone fruits are a rich source of biologically active compounds including carotenoids and flavonoids, phenolic compounds, vitamins A, C, and E and minerals that have antioxidant potential [3][4]. They also possess antimicrobial, anti-mutagenic, anti-inflammatory, cardio stimulating, anti-cancer, and antioxidant properties, among others [5][6]. Stone fruits are consumed fresh, dried, canned, or used to make liqueurs, brandy, and wines.…”
Section: Introductionmentioning
confidence: 99%